Revealing the intrinsic nature of the mid-gap defects in amorphous Ge2Sb2Te5 - Konstantinos Konstantinou (Nature Portfolio, 2019)
The structural origin of the mid-gap states responsible for the time-dependent resistance drift in phase-change materials is still under debate. Here the authors use machine learning and density functional theory to identify the structural motifs of the mid-gap defects in the prototypical Ge2Sb2Te5 phase-change alloy.